Epilepsy Surgery in Children Under Three Years of Age - Hannah Kristen Weiss; S. Kathleen Bandt (Pediatric Neurology Briefs Publishers, 2019)
Investigators from the University Medical Centre Schleswig-Holstein, Epilepsy Centre Kork, University of Freiburg, University Children's Hospital Heidelberg, Goethe University, and University Children's Hospital Zürich investigated seizure occurrence and cognitive development following epilepsy surgery by retrospectively studying 48 children under the age of three.